Design and analysis of a two-stage constant-torque flexure hinge (TS-CTFH) based on fixed-rotation constrained circular-arc segments - C. Li; L. Qiu; L. Qiu; Y. Yu; C. Jiang; S. Dai (Mechanical Sciences)
This study proposes a pseudo-rigid-body model (4bar-PRBM) for a fixed-rotation constrained circular-arc flexible segment and obtains characteristic parameters expressions using s as a variable. Then, the superposition principle of circular-arc segments is proposed, leading to the development of a novel two-stage constant-torque flexure hinge (TS-CTFH). With the dimension parameter s as a variable, TS-CTFH with different constant-torque output (Tid1 and Tid2) is optimized, which enhances the applicability of the hinge. The accuracy of theoretical analysis and the feasibility of the design scheme are ultimately validated through finite-element analysis (FEA) and testing. The novel TS-CTFH offers a proficient solution for design of grippers, joint rehabilitation devices, and assistive aids for human activities. Simultaneously, the four-bar PRBM offers a user-friendly tool for designing compliant constant-torque mechanisms (CCTMs) with circular-arc segments.